Endoscopic papillary balloon dilatation less than three minutes for biliary stone removal increases the risk of post-ERCP pancreatitis. - Chung-Kai Chou; Kuei-Chuan Lee; Jiing-Chyuan Luo; Tseng-Shing Chen; Chin-Lin Perng; Yi-Hsiang Huang; Han-Chien Lin; Ming-Chih Hou (PLoS ONE, 2020)
OBJECTIVES:The adequate duration for EPBD was unclear. Therefore, we aimed to investigate the effect of balloon dilatation duration of EPBD on the occurrence of PEP. METHODS:One hundred and ninety-eight patients with common bile duct (CBD) stone treated by EPBD were retrospectively recruited. The dilatation duration was determined according to adequate opening of the biliary orifice without bleeding. The clinical outcomes and complications of EPBD were recorded. RESULTS:We stratified the patients according to dilatation duration (Group A, <3 minutes; Group B, 3-5 minutes; Group C, ≥5 minutes). The group C patients had a higher proportion of large CBD stones (stones ≥10 mm) (33.3% vs. 26.8% vs. 53.5%, p = 0.01). Patients in group A had a significantly higher PEP rate than patients in group B (13.3 vs. 3.1, p = 0.032). There were no significant differences in perforation and bleeding rate among the three groups. Univariate and multivariate analyses showed that a dilatation duration of <3 minutes, CBD diameter < 10 mm and age ≤ 75 years were independent risk factors of PEP in post-EPBD patients. CONCLUSIONS:In patients receiving EPBD, dilatation duration <3 minutes, lower CBD diameter, and younger age were independent risk factors of PEP.